Model Layanan Bimbingan dan Konseling Komunitas pada Pasangan Menikah Dini di Desa Loang Maka, Kecamatan Janapria, Kabupaten Lombok - Zali, Samsul (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2024)
This research aims to develop and implement an effective community guidance and counseling service model to enhance the well-being of early-married couples in Loang Maka Village. Early married couples often face complex challenges in building and maintaining marital relationships. This service model is designed to provide holistic support through a community-based approach. This current research employs a qualitative approach with participatory action research, actively involving early married couples and the local community. Data are gathered through in-depth interviews, observations, and focus group discussions. Data analysis uses a thematic approach to identify thematic patterns emerging from the data. The research findings indicate that the community guidance and counseling service model effectively provides emotional, informational, and social support to early married couples. Active participation in community activities helps strengthen social bonds, enhance understanding of roles and responsibilities in marriage, and build positive social networks. The implementation of this model contributes positively to the improvement of the well-being of early married couples, reflected in increased happiness, marital resilience, and the quality of interpersonal relationships. The implications of this research include recommendations for implementing similar service models in other communities, taking into account different cultural and social contexts. This model is expected to serve as a foundation for the development of sustainable community guidance and counseling service programs, particularly to support early married couples in building healthy and happy families. (Penelitian ini bertujuan untuk mengembangkan dan mengimplementasikan model layanan bimbingan dan konseling komunitas yang efektif dalam meningkatkan kesejahteraan pasangan menikah dini di Desa Loang Maka. Pasangan menikah dini seringkali menghadapi tantangan kompleks dalam membangun dan memelihara hubungan perkawinan mereka. Model layanan ini didesain untuk memberikan dukungan holistik melalui pendekatan komunitas. Penelitian ini menggunakan pendekatan kualitatif dengan Participatory Action Research yang melibatkan partisipasi aktif dari pasangan menikah dini serta komunitas setempat. Data dikumpulkan melalui wawancara mendalam, observasi, dan focus group discussions. Analisis data dilakukan dengan menggunakan pendekatan tematik untuk mengidentifikasi pola-pola tematik yang muncul dari data. Hasil penelitian menunjukkan bahwa model layanan bimbingan dan konseling komunitas terbukti efektif dalam memberikan dukungan emosional, informasional, dan sosial kepada pasangan menikah dini. Partisipasi aktif dalam kegiatan komunitas membantu memperkuat ikatan sosial, meningkatkan pemahaman tentang peran dan tanggung jawab dalam perkawinan, serta membangun jejaring sosial yang positif. Implementasi model ini memberikan kontribusi positif terhadap peningkatan kesejahteraan pasangan menikah dini yang tercermin dari peningkatan kebahagiaan, ketahanan perkawinan, dan kualitas hubungan interpersonal. Implikasi dari penelitian ini adalah rekomendasi untuk penerapan model layanan serupa di komunitas-komunitas sejenis dengan mempertimbangkan konteks budaya dan sosial yang berbeda. Model ini diharapkan dapat menjadi landasan untuk pengembangan program layanan bimbingan dan konseling komunitas yang berkelanjutan, khususnya untuk mendukung pasangan menikah dini dalam membangun keluarga yang sehat dan bahagia.)